Internet of Things Based Solar Battery Monitoring System - Muzazanah, Annisa Tyas; Silaban, Freddy Artadima (Techno.Com, 2025)
There are two factors in the solar panel system that affect battery life, namely the battery discharge factor and the environmental factor temperature which the battery is placed in. The battery is damaged quickly if it is empty for a long time. The application of solar cells is widely used in street lighting and office buildings. However, in several research, it was observed there were deficiencies, namely both current and voltage measurements were still carried out manually using a multimeter so that the data taken had not been recorded continuously. The purpose of this research is to design the Solar Panel System Battery Telemetry to be a solution and to solve the problem of knowing the battery condition is monitored regularly. This system uses ESP32 as an IoT-based microcontroller that is connected to the internet. The website is used to display data from the output of a solar panel battery. Based on the results of the analysis and testing that has been carried out, the design system can run according to the initial concept and can record the current, voltage, and temperature in real-time resulting from the performance of the solar panel system. The results of measurements on 10 wp solar panel with an average power of 7.32 watts with a maximum current of 0.6 A and presentation of a solar panel efficiency of 0.82%. The use of solar panel system batteries with a power requirement of 9 Watt 12V (lamp load) does not experience losses during the charging process.   Keywords - Battery, Solar Panel, Internet of Things, Real Time, Website